Quality of Root Canal Filling Using a Bioceramic Sealer in Oval Canals: A Three-Dimensional Analysis - Penha da Silva, Poliana J.; Marceliano-Alves, Marília F.; Provenzano, José C.; Dellazari, Rafaela L. A.; Gonçalves, Lucio Souza; Alves, Flávio R. F. (European Journal of Dentistry, 2021)
Objectives The oval canals may be associated with inadequate debridement, which can affect the quality of the root canal filling, thus the treatment outcome. The aim of the present work was to compare the quality of oval canals fillings using EndoSequence BC sealer with the single-cone technique or cold lateral compaction.Materials and Methods Thirty-eight human single-rooted premolars with oval canals were instrumented to 1 mm from the apical foramen with hand nickel–titanium files, followed by circumferential filing with Hedstrom files. Teeth were paired into two groups based on their micro-computed tomography (CT) morphological parameters. Both groups were filled using EndoSequence BC sealer. The first used a single cone and the other with the cold lateral compaction technique. The voids volume was evaluated by micro-CT and the percentage was calculated for the total length and for the apical 5 mm of each canal. The Mann–Whitney U test was used to assess whether the surface area and obturation length differed significantly between the groups and to compare the percentage of voids for each technique.Results Both techniques resulted in less than 16% voids, with no statistically significant difference between them for the total canal length and for the apical 5 mm (p > 0.05).Conclusions The quality of the obturation performed with the single-cone technique was similar to that achieved with lateral compaction using EndoSequence BC sealer in oval canals.
Keywords: bioceramic sealers; EndoSequence BC sealer; root canal filling; single-cone technique